THE INFLUENCE OF THE INDEPENDENT CURRICULUM IMPLEMENTATION WORKSHOP ON IMPROVEMENT KNOWLEDGE OF PRESCHOOL EDUCATORS IN BOGOR CITY - Srie Harmiasih; Siti Nurhayati; Rice Anggrayni; Lelly Lenny; Rini Kumari; Vera Risman; Yayuk Winarsih; Nita Priyanti; Chandra Apriyansyah (Universitas Panca Sakti Bekasi, 2024)
The aim of this research is to determine the effect of training on IKM knowledge among PAUD teachers in Bogor City. The aim of this research is to determine the understanding abilities of PAUD teachers in Bogor City after implementing training and mentoring. The research subjects were PAUD teachers in Bogor City, which consists of six sub-districts, totaling 35 people. The results of this research indicate that training and mentoring have a significant effect on teachers' ability to understand and implement the Independent Curriculum. The achievements of this IKM Training and Mentoring can be seen from the pre-test results which show an average of 50% knowledge of PAUD teachers in Bogor City who took part in training on the Independent Curriculum, while the post-test results show an average increase of 76% obtained by participants with an increase understanding of the Independent Curriculum, both in terms of preparing the Operational Curriculum for Education Units, intracurricular learning, and the Project for Strengthening the Profile of Pancasila Students, as many as 95% of participants were able to create and compile the Operational Curriculum for Education Units according to the characteristics of each institution.